1935
DOI: 10.1002/cber.19350680147
|View full text |Cite
|
Sign up to set email alerts
|

Über Wuchsstoffe der Auxin‐ und der Bios‐Gruppe

Abstract: A u x i n -a , C18H3Z05, enthalt nach der analytischen Untersuchung eine Carboxylgruppe, drei alkoholische Hydroxyle, eine Doppelbindung und einen Kohlenstoffring. Von den vier Sauerstoffatomen des Auxi nsb, C,,H,,,O,, liegen zwei ebenfalls in einer Carboxylgruppe, eines in eineni alkoholischen Hydroxyl und eines in einer Ketogruppe vor. Auch Auxin-b enthalt eine Doppelbindung und einen Kohlenstoffring. Die M ti t a r o t a t io n , welche die Losungen beider Auxine zeigen, wird durch die Rildung von L a c t o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1936
1936
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The rapid development of the field has resulted, as would be expected, in the publication of a number of reviews and summaries. Such reviews have rarely more than temporary interest, and many of these are already only of historical value (Babicka, 1934;Cholodny, 1935a;Kogl, 1932 The newer and more extensive reviews are those of du Buy and Nuernbergk (1932, Erxleben (1935), von Guttenberg (1932,1933,1934,1935,1936), Heyn (1936), Jost (1935), Kogl (1935Kogl ( , 1935aKogl ( , 1936, Haagen Smit (1935), Stiles (1935), Thimann (1935, 19366), Went i (19356, 1936a), and F. A. F. C. Went^(1934C.…”
Section: Previous Reviews Of the Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid development of the field has resulted, as would be expected, in the publication of a number of reviews and summaries. Such reviews have rarely more than temporary interest, and many of these are already only of historical value (Babicka, 1934;Cholodny, 1935a;Kogl, 1932 The newer and more extensive reviews are those of du Buy and Nuernbergk (1932, Erxleben (1935), von Guttenberg (1932,1933,1934,1935,1936), Heyn (1936), Jost (1935), Kogl (1935Kogl ( , 1935aKogl ( , 1936, Haagen Smit (1935), Stiles (1935), Thimann (1935, 19366), Went i (19356, 1936a), and F. A. F. C. Went^(1934C.…”
Section: Previous Reviews Of the Fieldmentioning
confidence: 99%
“…It was then found that auxin b and, later, synthetic indole-3-acetic acid (Thimann and Koepfli, 1935;Kogl, 1935) were as active in root formation as the purest Rhizopus preparation.…”
Section: Root Formation 185 B Hormones and Root Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…of indole in the course of preparing indole ethylamine by the method of Majima and Hoshino (1925). Kogl (1935). Auxin-a is very stable towards acids, but is readily decomposed by alkalis.…”
Section: Synthesismentioning
confidence: 99%
“…Auxin-a lactone, distilled with potassium hydrogen sulphate, yielded a substance probably identical with auxin-b. (Kogl, 1935). Kogl (1938) has pointed out: "The formula of auxin-a contains seven asymmetric carbon atoms; any organic chemist knows what that implies.…”
Section: Synthesismentioning
confidence: 99%